TINDAK TUTUR LITERAL DAN TIDAK LITERAL DALAM UNGKAPAN PENOLAKAN ANTARA PENJUAL DAN PEMBELI - Nurjannah; Sahur Saerudin (Program Studi Sastra Indonesia Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
This study investigates literal and non-literal speech acts in rejection speech as well as the factors that influence these speech acts used by the public in cases of buying and selling that occur in the Kendari Jual Beli (KJB) Facebook group in Kendari City. The uniqueness of language in online buying and selling transactions in Kendari City is the basis for this research. When buyers and sellers carry out buying and selling transactions, there are various forms of rejection. Buyers use certain strategies to politely or subtly reject sellers' offers. In this way, misunderstandings can be avoided and a transaction agreement can be reached. Based on the research results, forms of rejection speech were found, namely literal and non-literal speech acts. Literal speech acts consist of direct and indirect literal speech acts. Non-literal speech acts are found in direct and indirect forms. Factors that influence the occurrence of rejection speech acts are the seller's slow response, the urgency of using the goods, the choice of payment method, mismatch with the description of the goods, the length of the goods delivery process, and weak controls in online buying and selling. Keywords: speech act, rejection, literal, non literal